Examining the Effects of Live Streamer and Product Characteristics on Purchase Intention: The Mediating Role of Emotional Trust in Social Commerce - Naswa Riantika; Wenny Pebrianti; Ana Fitriana; Ramadania; Bintoro Bagus Purmono (Journal of Educational Management Research, 2026)
This study aims to examine the influence of live streamer characteristics and product characteristics on purchase intention, with emotional trust serving as a mediating variable in the context of live streaming commerce for religious products. A quantitative approach was employed using a survey method involving 201 respondents who had previously watched religious product live streaming sessions on a short-video commerce platform. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that live streamer characteristics—comprising professionalism, attractiveness, and interactivity—have a positive and significant effect on both emotional trust and purchase intention. Similarly, product characteristics, including perceived quality, price fairness, and practicality, significantly influence emotional trust and purchase intention. Emotional trust was found to play a significant mediating role in strengthening the relationship between both live streamer characteristics and product characteristics and consumers’ purchase intention. These results imply that in emotionally sensitive product contexts, consumers’ purchase decisions are shaped not only by functional and economic considerations but also by the development of emotional trust fostered through credible and interactive live streaming experiences. This study contributes to the social commerce literature by extending the understanding of emotional trust mechanisms in live streaming environments involving high emotional and religious sensitivity products.